(6c-5)(6c+5)-(6c-5)^2 при c=11

0 голосов
100 просмотров

(6c-5)(6c+5)-(6c-5)^2 при c=11


Алгебра (57 баллов) | 100 просмотров
Дан 1 ответ
0 голосов

( 6c - 5)(6c + 5) - (6c - 5)² = 36c² - 25 - (36c² - 60c + 25) = 36c² - 36c² - 25 - 25 + 60c=
= 60c - 50
При c = 11:
60c - 50 = 60×11 - 50 = 660 - 50 = 610.

(34.2k баллов)
0

можете помочь еще, вот с этим (5d-1)(5d+1)-(5d+1) при d=110

0

а последняя скобка без квадрата?посмотрите

0

без

0

25d^2 - 1 - 5d - 1 = 25d^2 - 5d - 2 = 25*(110)^2 - 5*110 - 2 = 302500-550-2=301950-2=301948